On routing algorithms in the internet of vehicles: a survey - Arundhati Sahoo; Asis Kumar Tripathy (Connection Science)
Internet of Vehicles (IoV) provides an overview of the Internet of Things (IoT) and the Internet of Everything (IoE). Generally, it connects the different items, Vehicles, and Environments, which transfers data between the network. The various challenges associated with IoV are routing security and data transmission. It is a different form of the traditional intelligent transportation system, and thus, many researchers have studied routing protocols and their simulation tools. Finding all Such methodologies and their development are unavailable at a single source. Focusing on this objective, our research explores routing protocols within the Internet of Vehicles (IoV) context. Our study comprehensively reviews diverse routing algorithms and their associated assessment methodologies. To systematically categorise these protocols, we employ a multi-tiered taxonomy. Firstly, we classify them into three main groups based on their transmission strategies: unicast, geo-cast, and broadcast. Secondly, we categorise them into four classes: topology-based, position-based, map-based, and path-based. Thirdly, we organise them according to their dimensions, differentiating between 1-D, 2-D, and 3-D approaches. Finally, we classify these protocols based on their applicability to homogeneous or heterogeneous network environments. The combination of classical routing protocols with the emerging heterogeneous network paradigm is of particular interest in our research, representing a compelling area for future exploration. By presenting this extensive framework, we aim to inspire researchers in the IoV field to develop innovative and efficient routing protocols and technologies.